Fully automatized apparatus for determining speed of sound for liquids in the temperature and pressure interval (283.15–343.15) K and (0.1–95) MPa. (January 2017) - Yebra, Francisco; Troncoso, Jacobo; Romaní, Luis
Graphical abstract: Highlights: An apparatus for measuring speed of sound of liquids is described. Pressure and temperature control is fully automatized. Uncertainty of the measurements is estimated in 0.1%. Comparison with literature data confirms the reliability of the methodology. Abstract: An instrument for determining the speed of sound as a function of temperature and pressure for liquids is described. It was totally automatized: pressure and temperature values are controlled and time of flight of the ultrasonic wave data were acquired using a digital system which automatically made all required actions. The instrument calibration was made only at atmospheric pressure using high quality data of water and methanol. For higher pressures, the calibration parameters were predicted using a model for the high pressure cell, through finite-element calculations (FEM), in order to realistically determine the changes in the cell induced by the compression. Uncertainties in pressure and temperature were 20 mK and 0.1 MPa, respectively and in speed of sound it was estimated to be about 0.1%. The speeds of sound for water, methanol, hexane, heptane, octane, toluene, ethanol and 1-propanol were determined in the temperature and pressure ranges (283.15–343.15) K and (0.1–95) MPa. Comparison with literature data reveals the high reliability of the experimental procedure.